2018
DOI: 10.18805/lr-381
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and antioxidant activity of adzuki bean cultivars

Abstract: The phenolic compounds and radical scavenging activity of ethanolic extracts of five adzuki beans were evaluate according to cultivar. The predominant phenolic acids in five cultivars of adzuki bean were (+)-catechin and gallic acid. Antioxidant capacities were determined using 2,2-diphenyl-1-picrylhydrazyl and 2,2-azinobis (3-ethylbenothiazoline-6-sulphonic acid) diammonium salt, and reducing power was positively enhanced according to the total polyphenolic content. In a cell-based assay, adzuki beans showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…There are no other data from in vitro studies by other authors with bean extracts. However, Vila-Donat et al [ 34 ] reported synergistic cytoprotective effects against cytotoxicity induced by alternariol on Caco-2 cells exposed to an extract obtained from other types of legumes, such as lentils.…”
Section: Resultsmentioning
confidence: 99%
“…There are no other data from in vitro studies by other authors with bean extracts. However, Vila-Donat et al [ 34 ] reported synergistic cytoprotective effects against cytotoxicity induced by alternariol on Caco-2 cells exposed to an extract obtained from other types of legumes, such as lentils.…”
Section: Resultsmentioning
confidence: 99%
“…Catechin and epicatechin were extracted and analyzed as previously reported [42], with slight modification. Powdered rice samples (0.01 g) were extracted with 200 µL of 80% ethanol containing 1.2 M HCl.…”
Section: Extraction and Analysis Of (+)-Catechin And (−)-Epicatechinmentioning
confidence: 99%
“…Besides, Lee et al reported adzuki bean extracts using 80% ethanol includes gallic acid, catechin, ferulic acid, and hesperidin, etc. [ 15 ]. Accordingly, various functionalities of black soybeans and adzuki beans have been reported.…”
Section: Introductionmentioning
confidence: 99%